Global Television: An Introduction - Barker, Chris (Wiley-Blackwell, 1997)
This text provides readers with useful summaries and evaluations of key arguments relating to the development of television as an industry across the globe and its potential cultural impact. There is a continual insistence in the book on the need to connect issues of industry with those of culture.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 2-Étude des industries culturelles; 2-Étude des représentations; 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); _Nettoyé